2005
DOI: 10.1051/0004-6361:20041654
|View full text |Cite
|
Sign up to set email alerts
|

Absence of linear polarization in Hαemission of solar flares

Abstract: Abstract. High sensitivity observations of Hα polarization of 30 flares of different sizes and disk positions are reported. Both filter and spectrographic techniques have been used. The ZIMPOL system eliminates spurious polarizations due to seeing and flat-field effects. We didn't find any clear linear polarization signature above our sensitivity level which was usually better than 0.1%. The observations include an X17.1 flare with gamma-ray lines reported by the RHESSI satellite. These results cast serious do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 21 publications
4
28
1
Order By: Relevance
“…But no observation to date employed chromospheric polarimetry to unambiguously trace the magnetic field changes. Former chromospheric polarization measurements mostly focused on linear polarization and the search for "impact" polarization (e.g., Henoux et al 1990;Bianda et al 2005;Judge et al 2015). In this paper, we report the first direct observations of chromospheric magnetic field changes that were observed through spectropolarimetry of the Ca II 8542Å line during an X-class flare and we compare them to the photospheric changes of the same flare.…”
mentioning
confidence: 99%
“…But no observation to date employed chromospheric polarimetry to unambiguously trace the magnetic field changes. Former chromospheric polarization measurements mostly focused on linear polarization and the search for "impact" polarization (e.g., Henoux et al 1990;Bianda et al 2005;Judge et al 2015). In this paper, we report the first direct observations of chromospheric magnetic field changes that were observed through spectropolarimetry of the Ca II 8542Å line during an X-class flare and we compare them to the photospheric changes of the same flare.…”
mentioning
confidence: 99%
“…Trujillo Bueno et al (2002) were also able to determine the magnetic field vector of the observed filament by modeling the Stokes Q and U profiles (produced by the forward-scattering Hanle effect) and the Stokes V profiles (caused by the longitudinal Zeeman effect). Observations in filaments carried out by Bianda et al (2006) in the H i 6563 Å and He i 5876 Å lines showed similar polarization signatures.…”
Section: Introductionmentioning
confidence: 53%
“…Another surprising result was that no coherent radio emission was detected in 17% of hard X-ray flares , since both emissions are produced by electrons of similar energy and occasionally coincide with subsecond accuracy (Arzner & Benz 2005). A puzzle is also the absence of linear polarization in Ha emission, which limits the anisotropy of energetic protons and refutes earlier positive reports (Bianda et al 2005).…”
Section: Rhessi Observationsmentioning
confidence: 78%